PEMANFAATAN MEDIA WORDWALL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V DI MADRASAH IBTIDAIYAH SWASTA AL-WASHLIYAH SEI MENCIRIM - Siti Suharni Simamora, Yuni Asri Ningratri, Irhamuddin, Wayan Iqbal, Nashwa Ghifanny Pulungan (JURNAL BIMA, 2026)
Student motivation and response are important factors in supporting the success of the learning process in elementary schools. However, based on the results of initial observations in Class V MIS Al-Washliyah Sei Mencirim, it was found that student responses were still low, marked by a lack of student activity and enthusiasm in participating in learning. Therefore, this community service activity aims to improve student responses and learning motivation through the use of digital wordwall media. This activity was carried out on 24 fifth grade students. The methods used included observation, interviews, and the use of learning technology in the form of wordwall media. Wordwall media was applied in the learning process by presenting materials and questions in the form of interactive games. The results of the activity showed that the use of wordwall media was able to improve student responses, seen from increased student activity in answering questions, involvement during learning, and enthusiasm in participating in learning activities. In addition, the results of interviews with teachers and students showed that learning became more interesting and enjoyable. Thus, the use of digital wordwall media can be used as an alternative effective learning media to improve student responses and learning motivation in elementary schools.